Aspirations and Financial Decisions : Experimental Evidence from the Philippines - McKenzie, David; Mohpal, Aakash; Yang, Dean (World Bank, Washington, DC, 2021)
A randomized experiment among poor entrepreneurs tested the impact of exogenously inducing higher financial aspirations. In theory, raising aspirations could have positive effects by inducing higher effort, but could also reduce effort if unmet aspirations lead to frustration. Treatment resulted in more ambitious savings goals, but nearly all individuals fell far short of reaching these goals. Two years later, treated individuals had not saved more, and actually had lower borrowing and business investments. Treatment also reduced belief in the amount of control over one’s life. Setting aspirations too high can lead to frustration, leading individuals to reduce their economic investments.